Correction: Discovery of a 19F MRI sensitive salinomycin derivative with high cytotoxicity towards cancer cells. Issue 45 (18th May 2016) - Shi, Qiuyan; Li, Yu; Bo, Shaowei; Li, Xiaofei; Zhao, Peng; Liu, Qi; Yang, Zhigang; Cong, Hengjiang; Deng, Hexiang; Chen, Mingnan; Chen, Shizhen; Zhou, Xin; et al.
Abstract : Correction for 'Discovery of a 19 F MRI sensitive salinomycin derivative with high cytotoxicity towards cancer cells' by Qiuyan Shi et al., Chem. Commun., 2016, 52, 5136–5139.